2020
DOI: 10.1002/pmrj.12398
|View full text |Cite
|
Sign up to set email alerts
|

Patients with Symptomatic Hip Osteoarthritis Have Altered Kinematics during Stair Ambulation

Abstract: Background Osteoarthritis (OA) is a degenerative joint disease. Understanding contributing factors to slowing or stopping disease progression is crucial. There has been no research describing lower extremity kinematics of the hip, knee, and ankle during stair ambulation in individuals with hip OA. Objective To explore the differences in lower extremity kinematics between participants with clinical and morphological findings of hip OA and controls. Design A cross‐sectional study. Setting Clinical research labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…There is a general understanding that the rotational alignment of the whole lower limb plays a critical role in the onset of hip pathologies ( Eckhoff, 1994 ; Keshmiri et al, 2016 ). Additionally, several kinematic compensatory strategies can be adopted at the hip ( Bruderer-Hofstetter et al, 2015 ; Alexander et al, 2019 ), as a consequence of either pain avoidance ( Leigh et al, 2016 ; Popovic et al, 2020 ) or lever arm dysfunction, particularly of the hip abductors ( Arnold et al, 1997 ; van der Krogt et al, 2012 ; Boyer et al, 2016 ). Moreover, modeling excessive femoral antetorsion was shown to alter magnitude and orientation of predicted joint contact forces in pediatric pathological populations ( Bosmans et al, 2014 ; Passmore et al, 2018 ), as well as in typically developing children ( Kainz et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…There is a general understanding that the rotational alignment of the whole lower limb plays a critical role in the onset of hip pathologies ( Eckhoff, 1994 ; Keshmiri et al, 2016 ). Additionally, several kinematic compensatory strategies can be adopted at the hip ( Bruderer-Hofstetter et al, 2015 ; Alexander et al, 2019 ), as a consequence of either pain avoidance ( Leigh et al, 2016 ; Popovic et al, 2020 ) or lever arm dysfunction, particularly of the hip abductors ( Arnold et al, 1997 ; van der Krogt et al, 2012 ; Boyer et al, 2016 ). Moreover, modeling excessive femoral antetorsion was shown to alter magnitude and orientation of predicted joint contact forces in pediatric pathological populations ( Bosmans et al, 2014 ; Passmore et al, 2018 ), as well as in typically developing children ( Kainz et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Peak external rotation was significantly reduced during stance phase (56) but not during swing phase (44). Transverse hip ROM was significantly reduced (44).…”
Section: Stair Ascentmentioning
confidence: 88%
“…Results not included in the meta-analysis showed no differences in peak hip extension during the gait cycle (44) or during the stance phase (56). Peak flexion was significantly reduced in the swing phase (44).…”
Section: Stair Ascentmentioning
confidence: 89%
See 1 more Smart Citation
“…We believe that actual structural progression may have been the factor, in our study, preventing objective functional improvement, which manifests in the outcome of specific PBTs. It has been repeatedly reported that increased severity of morphological signs in subjects with HOA is associated with an increased load on the joint resulting in abnormal kinetics during walking or stair ambulation [28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%